IMPACT OF SELECTED FIRM-SPECIFIC CHARACTERISTICS ON FINANCIAL PERFORMANCE OF NIGERIAN LISTED INSURANCE USING CARAMELS FRAMEWORK - ALIU, Ismaila Daudu; Qadir Folorunsho DAUDA; Rukayat Bukola ADEJARE; Bashirat O OLOYIN-ABDULHAKEEM (Malete Journal of Accounting and Finance, 2022)
Insurance sub-sector of financial services serve as the backbone of economic growth through efficient resource allocation, reduction of business risks and spread of financial risk. However, the overall financial performance of Nigerian insurance industry is low evidenced with pitiable penetration rate and contribution to Gross Domestic Product of Nigeria. This has been attributed to appalling influences of firms’ specific characteristics such age, size, leverage and tangibility among others. Therefore, this study evaluates the impact of firm specific characteristics on financial performance of Nigeria listed insurance companies. The study employed Expost-facto research design. Population of the study include all the 22 listed insurance companies in Nigeria from 2012 to 2021. Secondary data gathered from annual reports was analysed with descriptive and inferential statistics. The descriptive statistics showed that the data are normally distributed and there is existence auto-correlation. The results of Serially Correlated Disturbance Random Effects revealed that three out of the four firm-specific characteristics employed in this study were statistically significant with CARAMELS financial performance indicator. The study concludes that age and leverage status of listed insurance companies in Nigeria significantly and positively influences asset quality while size of listed insurance companies significantly and positively influences the capital adequacy, management efficiency and solvency. Therefore, the study recommends that management of listed insurance companies should invest more of their capital obtained through external long-term sources on asset in order to achieve capital adequacy, management efficiency and solvency status of listed insurance companies in Nigeria.